2017
DOI: 10.1037/str0000031
|View full text |Cite
|
Sign up to set email alerts
|

Stress, work ability, and an aging workforce: A study among women aged 50 and over.

Abstract: Work ability is a central concept in studies concerning the health of the aging workforce. The aim of the present study was to understand the role of work ability in the Job Demands-Resources model and, specifically, to establish whether and through which mechanisms it operates as a personal resource in the health-impairment process. Two-hundred and 2 female kindergarten teachers aged 50 and over completed self-reporting questionnaires. Data analyses were performed using structural equation model (SEM) and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…Global research also notably contributed to identifying new buffer-type resources. An enrichment to the Dutch-promoted job-demands resources model (Bakker et al 2014, Demerouti et al 2001, for instance, validates work ability perception as a personal resource that mediates the positive relationship between job demands and emotional exhaustion among older Italian kindergarten teachers (Viotti et al 2017). Perceived organizational support of personal strengths, including professional know-how and talent, was identified as a significant buffer against the resource-depleting effect of high workload and high emotional demands in a large sample of Dutch health professionals (van Woerkom et al 2016).…”
Section: Dynamics and Contingenciesmentioning
confidence: 59%
“…Global research also notably contributed to identifying new buffer-type resources. An enrichment to the Dutch-promoted job-demands resources model (Bakker et al 2014, Demerouti et al 2001, for instance, validates work ability perception as a personal resource that mediates the positive relationship between job demands and emotional exhaustion among older Italian kindergarten teachers (Viotti et al 2017). Perceived organizational support of personal strengths, including professional know-how and talent, was identified as a significant buffer against the resource-depleting effect of high workload and high emotional demands in a large sample of Dutch health professionals (van Woerkom et al 2016).…”
Section: Dynamics and Contingenciesmentioning
confidence: 59%
“…A larger number of older workers implies, for example, an increasing number of people at work with minor and major health problems that occur more frequently after 55 years of age ( Knoche et al, 2012 ; Maricchio et al, 2013 ). In this view, over the next several years organizations will be faced with a prevalence rate of chronic diseases (e.g., musculoskeletal disorders, diabetes, or cardiovascular diseases, cancer) close to 20/30% of the entire workforce ( Gragnano et al, 2017 ), with an attendant strong impact on work ability (WA) ( Camerino et al, 2006 , 2008a ; Golubic et al, 2009 ; Milosevic et al, 2011 ; Carel et al, 2012 ; Monteiro et al, 2012 ; Loera et al, 2013 ; Guglielmetti et al, 2014 ; Leijten et al, 2014 ; Converso et al, 2015b ; Viotti et al, 2017a ). Therefore, aging requires workers’ health and diseases to be reconsidered from the perspective of a “work-health balance” (WHB: Miglioretti et al, 2016 ; Gragnano et al, 2017 ) to promote interventions (age management policies, job design from an ergonomic perspective, job redesign addressing psychological changes: Truxillo and Zaniboni, 2017 ) aimed at supporting workers’ mental and physical health, WA, and job productivity over the entire working lifecycle, and over: higher-quality jobs (e.g., complex and challenging works) can impact cognitive development, reducing the risk of dementia and enhancing cognitive ability in later life ( Andel et al, 2005 ; Finkel et al, 2009 ), and in general strengthening physical and psychological health during work-life is of great relevance even for late-life health and function ( Nilsen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ilmarinen and Ilmarinen (2015) explained that this decline is due to the imbalance between the individual resources and the demands of the job, namely the work and the organizational context are not aligned to the age-related changes in personal resources. Poor WA is predictive of sickness absences, early retirement, disability pension, intention to leave ( Goedhard and Goedhard, 2005 ; Camerino et al, 2006 ; Monteiro et al, 2006 ; Emberland and Knardahl, 2015 ), work stress, depression ( Tuomi et al, 1991 ; van den Berg et al, 2008 ; Bethge et al, 2009 ; Godinho et al, 2016 ), and emotional exhaustion ( Viotti et al, 2017a ). Conversely, good WA is associated with a high quality of work, high productivity, and enjoyment of time at work.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Van den Berg et al [8,9] observed that the negative effects on work performance of decreased work ability could be partly counterbalanced by increased job control, while McGonagle et al [20] observed that skill discretion moderated the negative relationship between job demands and work ability. More generally, the literature highlighted that decision authority [21][22][23][24][25] and skill discretion [23,[25][26][27][28] were very important dimensions in promoting work ability and well-being at work. The lifespan perspective on work design [23] proposed that some job resources had a stronger positive relationship with indicators of occupational well-being among older workers.…”
Section: Job Control and Work Abilitymentioning
confidence: 99%
“…The lifespan perspective on work design [23] proposed that some job resources had a stronger positive relationship with indicators of occupational well-being among older workers. More specifically, the literature showed that job control [21][22][23][24]27,28] was a very important resource for work ability, and in particular, for older workers.…”
Section: Job Control and Work Abilitymentioning
confidence: 99%